2016
DOI: 10.1126/science.aad2646
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community assembly and metabolic function during mammalian corpse decomposition

Abstract: Vertebrate corpse decomposition provides an important stage in nutrient cycling in most terrestrial habitats, yet microbially mediated processes are poorly understood. Here we combine deep microbial community characterization, community-level metabolic reconstruction, and soil biogeochemical assessment to understand the principles governing microbial community assembly during decomposition of mouse and human corpses on different soil substrates. We find a suite of bacterial and fungal groups that contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
384
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 407 publications
(431 citation statements)
references
References 27 publications
18
384
2
Order By: Relevance
“…At least some of these microbes are opportunistic members of the livinghuman microbiome (5). "Most likely there are some microbes that are just waiting for us to keel over," Metcalf says.…”
Section: Flies In the Ointment?mentioning
confidence: 99%
See 1 more Smart Citation
“…At least some of these microbes are opportunistic members of the livinghuman microbiome (5). "Most likely there are some microbes that are just waiting for us to keel over," Metcalf says.…”
Section: Flies In the Ointment?mentioning
confidence: 99%
“…In a previous collaboration with Bucheli, Metcalf found that at least a small percentage of the postmortem microbiome may also be deposited by flies colonizing a body (5). In one study Bucheli designed, she and her team found that the community of microbes on flies visiting recently placed bodies varied in diversity and abundance across different seasons and even across the same seasons in different years.…”
Section: Flies In the Ointment?mentioning
confidence: 99%
“…To date there is limited research documenting microbial succession on a corpse. However, recent research indicates that microbial communities change significantly, following a predictable timescale during decomposition [15]. The initial bacterial community varies with the age [16] and health [17] of the victim, the location on the body [18], environmental temperature and humidity [19], and the season [20][21].…”
Section: Introductionmentioning
confidence: 99%
“…As decomposition continues, the microbial community changes as bacteria move from sites internal to the body to locations on the surface, and are transferred from the soil, scavengers and insects [15,17,23]. Different species of bacteria are known to be associated with different stages of the decomposition process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation